Analysis of Literacy Movement on Reading Ability of Grade II Elementary School Students - Ikhwatul Fadilah; Widia Nur Jannah; Hanikah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled "Analysis of Literacy Movement on Reading Ability of Grade II Students at UPTD SD Negeri 1 Weru Lor". The purpose of this study was to analyze the implementation of the School Literacy Movement (GLS) and its impact on the reading ability of grade II students. The method used was a descriptive qualitative approach, with data collection through interviews, observations, and documentation. The results of the study showed that the implementation of GLS at UPTD SD Negeri 1 Weru Lor had been carried out by actively involving teachers and students. Literacy activities were carried out every day, both at the beginning and in the middle of learning, with various methods such as reading together, reading aloud, and reading silently. However, there are still challenges in improving students’ reading ability, such as low reading interest and limited interesting reading materials. Supporting factors for the implementation of GLS include support from the principal, availability of books, and adequate facilities. However, there are also inhibiting factors such as lack of parental participation and minimal time allocation for reading activities. This study is expected to contribute to the development of more effective and sustainable literacy strategies in elementary schools, as well as improving students’ reading ability.